2007
DOI: 10.2215/cjn.02550607
|View full text |Cite
|
Sign up to set email alerts
|

Is the Declining Use of Long-Term Peritoneal Dialysis Justified by Outcome Data?

Abstract: In the past decade, peritoneal dialysis use among patients with end-stage renal disease has declined in many countries. Studies from the United States indicate that many academic centers do not have adequate resources to train fellows, most incident dialysis patients are not offered peritoneal dialysis, and more than half of dialysis clinics do not have the infrastructure to support peritoneal dialysis. Some are concerned that the outcomes of peritoneal dialysis and maintenance hemodialysis patients may not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 84 publications
1
57
1
Order By: Relevance
“…A large number of studies have examined the relationship of dialysis modality to patient survival with or without transplantation (1,27,28). Although there is no significant difference in 5-year survival of patients in contemporary cohorts, many of the earlier studies have shown a lower risk for death in the first 1-3 years after the start of dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have examined the relationship of dialysis modality to patient survival with or without transplantation (1,27,28). Although there is no significant difference in 5-year survival of patients in contemporary cohorts, many of the earlier studies have shown a lower risk for death in the first 1-3 years after the start of dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies were limited by lack of statistical power, lack of consideration of nonproportional hazards and competing risks, and uncertain relevance of outcomes observed over a decade ago to contemporary dialysis practice. The relevance to current practice is particularly important in view of observations that outcomes in PD patients have improved over time relative to those in HD patients (18,28).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Poor glycaemic control (glycosylated haemoglobin [HbA 1c ] !8%) in PD patients appears to be associated with higher mortality. 9 Glucose absorption from PD solutions also contributes to the harmful effects on the metabolic profile and hydration status. [10][11][12] Some observational studies showed a higher risk for death in older diabetic PD patients compared with those on haemodialysis.…”
Section: Introductionmentioning
confidence: 99%